ORGANIZATIONAL CAPACITY AND FINANCIAL MANAGEMENT PERFORMANCE OF LOCAL GOVERNMENT - Arifai, Muhammad; Mustaqim, T.; Hasan, Diana (JURNAL KEBANGSAAN, 2015)
This study investigates the relationship between organizational capacities and financial implementation performance on Local Government. This study addresses the question of whether organizational capacities as measured by financial literacy, dynamic capability, strategic planning, goal orientation, budget allocation, and control and monitor impact directly on financial implementation performance. Using the data from North of Aceh and Lhokseumawe City, therefore, the results shown four variables are significant impact while two variables are not significant. Based on results suggested both Local Governments i.e., North of Aceh and Lhokseumawe city have generated similar focus on four factors and significantly impact to financial performance. However, two others variables such as DinCap and StratPlan are not significant. In the environment uncertainty, DinCap and StatPlan are appropriate tools to recombine functional competence of the organization particularly in financial implementation stage. The result implies empirically shown both Local Governments failed to obtain WTP opinion and it may because weak of associate of Dincap and StratPlan operation with rapid change of the environment.Â Keywords:Â  organizational capacities, financial management performance.